Lecture16 - f x = e 2 x cos x at x = 0 Note the following If f x = e ax for constant a f x = ex d dx ±(1 e x 2 e x ² ex d dx r 1 e 2 x 1 ± e 2 x

Info iconThis preview shows pages 1–13. Sign up to view the full content.

View Full Document Right Arrow Icon
Lecture 16: The Chain Rule (Sec. 3.4) Consider the functions f ( x ) = tan ± ±x 2 ² and h ( x ) = p x 2 + 4 x ± 5. How to di±erentiate? NOTE: f and h are composite functions.
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Theorem (The Chain Rule) : If g is di±erentiable at x and f is di±erentiable at g ( x ), then the composite function F = f ± g = f ( g ( x )) is di±erentiable and F 0 ( x ) = Alternatively, if y = f ( u ) and u = g ( x ) are di±eren- tiable functions, then
Background image of page 2
ex. Find d dx (1 + tan x ) 10 ex. If h ( x ) = p x 2 + 4 x ± 5, ±nd h 0 ( x ).
Background image of page 3

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
These are examples of the following: Power Rule combined with the Chain Rule If n is any real number and u = g ( x ) is di±erentiable, then or ex. If g ( x ) = 4 4 p (3 ± 2 x 2 ) 3 ²nd g 0 ( x ).
Background image of page 4
ex. If f ( x ) = (2 x +3) 4 (2 ± x ) 3 , ±nd f 0 ( x ). At which x -values does the graph of f ( x ) have a horizontal tangent line?
Background image of page 5

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
ex. Find and simplify f 0 ( x ) if f ( x ) = x 2 p 3 ± 2 x . Write the equation of the tangent line to f ( x ) at x = 1.
Background image of page 6
Derivatives involving Exponential Functions ex. Find: d dx ( e ± 2 x 2 +1 ) ex. Find the equation of the tangent line to
Background image of page 7

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 8
Background image of page 9

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 10
Background image of page 11

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 12
Background image of page 13
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: f ( x ) = e 2 x cos x at x = 0. Note the following: If f ( x ) = e ax for constant a , f ( x ) = ex. d dx ± (1 + e x ) 2 e x ² ex. d dx r 1 + e 2 x 1 ± e 2 x We have the following important result: For base a > 0, d dx a x = ex. Find the slope of the tangent line to f ( x ) = 4 6 x ± cos x at x = ± . ex. Find g ( x ) for g ( x ) = 3 4 x . Derivatives involving trigonometric functions ex. Find f ( x ) if f ( x ) = tan ± ±x 2 ² : ex. Find the equation of the tangent line to y = sin 3 x cos 3 x at x = ± 2 . ex. Find the derivative of f ( x ) = sec 2 (sin 4 x ). Additional Example ex. If g ( x ) = p x 2 + 3 p 2 x + 1, ±nd g (4)....
View Full Document

This note was uploaded on 02/10/2011 for the course MAC 2311 taught by Professor All during the Spring '08 term at University of Florida.

Page1 / 13

Lecture16 - f x = e 2 x cos x at x = 0 Note the following If f x = e ax for constant a f x = ex d dx ±(1 e x 2 e x ² ex d dx r 1 e 2 x 1 ± e 2 x

This preview shows document pages 1 - 13. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online